An Analysis of Employee Empowerment and Organizational Culture on Employee Organizational Commitment in Regional 1 PT Pelindo (Persero) - Syariful Mahya; Feby Milanie; Muhammad Isa Indrawan (CERED Indonesia Institute, 2022)
The purpose of this research is to knowing the effect of employee empowerment and organization culture on commitment organization employee of PT. Pelindo (Persero) Medan with motivation as intervening variable. In this research consist of two dependent variables and two independent variables. These variables are commitment organization (Y2), Motivation (Y1), Employee Empowerment (X1) and Organization Culture (X1). The research used 124 respondents as samples whom taken from 11 department of PT. Pelindo (Persero) Medan. The research used descriptive method which gave questionnaire to respondents. From analyze data used path analyze with SPSS (Service for Product and Statistic Solution). The result of the research show that partially employee empowerment (X1) with value t hitung 3,510 , organization culture (X2) with value t hitung 7,783 positively and significantly took effect to commitment organization (Y1). Partially also concluded that motivation (Y1) with value t hitung 2,814 took effect positively and significantly to commitment organization (Y2).